EFEKTIVITAS EDUKASI KESEHATAN “AYO BERSIH AYO SEHAT” MENGENAI CUCI TANGAN PAKAI SABUN DAN PEMILIHAN JENIS SAMPAH PADA SISWA DI SDN 13 RAMBANG - Najma Hoirunnisa; Adelina Irmayani Lubis; Dinda Putri Maharani; Zurriyati Azka Ramadhani; Nazila Safitri; Popi Anjani; Siti Mahaida; Mukaddimah Najwa Al Yusna; Arista Miranda Putri; Sarila Diva Dea Ariesty; Fatimah Nur Mutmainah; Naura Rizky Deprianty; Ari Tri Gusti (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2025)
Health education activities are one of the promotive and preventive efforts in instilling the values ​​of clean and healthy living behavior (PHBS) from an early age. In the context of implementing the community service program, an educational activity with the theme